Adoption of Improved Potato Technology in Chitwan, Nepal - Ghimire, Narishwar (Economic Journal of Nepal, 2005)
A study was conducted in 2004/05 to evaluate the status of adoption of potato technology in Gunjanagar and Shukranagar VDCs of Chitwan district, Nepal. A sample size of 73 household was selected by using simple random sampling technique. The sample households comprised about 90 percent of the total commercial potato growers in the selected VDCs. Based on the analysis by using a multivariate logistic regression model it was found out that number of extension visit per year to the farmers, TV ownership and training on improved potato cultivation package to the farmers had significant positive impact on the adoption of potato technology. The probability of adoption seemed to be increased upon increasing the number of extension visit, providing training on potato growing packages and TV ownership ceteris paribus. A vast majority of the farmers were found to be using uncertified potato seed for cultivation which caused the lower potato yield. Majority of the farmers were found to be dissatisfied with the available potato varieties indicating the need for more late blight resistant, high yielding, low-input requiring, early maturing and inclement weather resistant red potato varieties.Economic Journal of Nepal Vol.28(3) 2005 pp.188-199